Wisdom and Torah the reception of 'Torah' in the wisdom literature of the Second Temple period - Schipper, Bernd Ulrich, 1968-; Teeter, David Andrew (Leiden : BRILL, 2013)
Taking the concepts of wisdom and Torah in the book of Deuteronomy as a point of departure, the essays of the present collection examines the relationship between wisdom and Torah in Wisdom literature of the Second Temple period.
The blinded eyes of the wise : sapiential tradition and Mosaic commandment in Deut 16:19-20 -- Law and wisdom according to Deut 4:5-8 -- When wisdom is not enough : the discourse on wisdom and Torah and the composition of the Book of Proverbs -- Job in conversation with the Torah -- "Fear God and keep His commandments" : could Qohelet have said this? -- Yahweh's Torah and the praying "I" in Psalm 119 -- Half way between Psalm 119 and Ben Sira : wisdom and Torah in Psalm 19 -- Torah and sapiential pedagogy in the Book of Ben Sira -- "Wisdom" and "Torah" in the Book of Baruch.
Print version record.
Keywords: Bible. -- Criticism, interpretation, etc. -- Congresses; Bible; Wisdom literature -- Criticism, interpretation, etc. -- Congresses; Apocryphal books (Old Testament) -- Criticism, interpretation, etc. -- Congresses; Judaism -- History -- Post-exilic period, 586 B.C.-210 A.D. -- Congresses; RELIGION -- Biblical Studies -- Old Testament; RELIGION -- Judaism -- Sacred Writings; Apocryphal books (Old Testament); Judaism -- Post-exilic period (Judaism); Wisdom literature; 586 B.C. - 210 A.D.; Electronic books; Conference papers and proceedings; Criticism, interpretation, etc; History; Electronic books